Prarancangan Pabrik Sorbitol Dengan Proses Hidrogenasi Katalitik Kapasitas 65.000 Ton/Tahun - Maryanto, Duwi, Tri Widayatno,S.T., MS.c., Ph.D, M Mujiburrohman, S.T., M.T., Ph.D (2017)
Sorbitol is an intermediate product obtained by the reaction of glucose with hydrogen gas. In the chemical industry sorbitol used for additional material in the final product. Sorbitol is widely used as a substitute artificial sweetener glucose for diabetics, as raw material for the manufacture of vitamin C. In the cosmetics industry is used as an ingredient in creams, ointments, emulsions, lotions, gels and toothpaste. Factory sorbitol and glucose feedstocks with hydrogen palnned to be established industrial area of Kendal, Central Java with a capacity of 65,000 tons per year. The factory is expected to reduce the need for imported Indonesian sorbitol and sufficiency in the country and increase the export of Indonesian sorbitol. The process of making sorbitol by catalytic hydrogenation process is carried out in a fixed bed reactor with the aid of Raney nickel catalyst. The reaction takes place in the manufacture of sorbitol liquid-gas phase, is exothermic. The operating conditions of the reactor is designed to be nonisothermal at operating temperature range 130-180oC with no energy is added or taken (adiabatic) and an operating pressure of 70 atm. For a plant capacity of 65,000 ton per year sorbitol and glucose feedstocks need for 11712.9602 kg / hour and hydrogen as much as 66.2697 kg / hour and requires activated carbon for purification as much 1177.9230 kg / hour. Factory sorbitol has a support unit that processes the utility unit includes water supply units, steam and electricity. The water requirement for the utility plant as much 5020.6295 kg / hour obtained from the river, steam provider unit capable of producing steam at 6459.715 kg / hour for the electricity needs of the plant as much as 370.9852 kWh obtained from PLN. The factory also has a reserve of 500 kWh generator with diesel fuel as much as 632 liters / hour, which is used if there are problems of supply of electricity. The need of area used for the establishment of 65,600 m2 factory sorbitol and require a staff of about 139 people. Factory sorbitol choose a limited liability company as a form of business entity. Sorbitol factory in operation for 330 days per year. Factory sorbitol require Rp 472,841,072,286.65 fixed capital and working capital of RP 203,903,938,277.50. Economic analysis of sorbitol plant showed a profit before tax of Rp 182,571,489,244.74 per year and after tax profit to Rp 136,928,616,933.55 per year. Percent Return On Investment (ROI) before tax after tax 39.23% and 29.42%. Pay Out Time (POT) before tax and after tax of 2.03 years 2.54 years. Break Even Point (BEP) which is equal to 52.75%, Shut Down Point (SDP) amounted to 37.69%. Discounted Cash Flow (DCF) accounted for 25.24%. Consideration of the economic aspect of the analysis we can conclude that sorbitol feasible to set up factories.